2023
DOI: 10.1007/s00415-023-11587-4
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 severity is related to poor executive function in people with post-COVID conditions

Abstract: Patients with post-coronavirus disease 2019 (COVID-19) conditions typically experience cognitive problems. Some studies have linked COVID-19 severity with long-term cognitive damage, while others did not observe such associations. This discrepancy can be attributed to methodological and sample variations. We aimed to clarify the relationship between COVID-19 severity and long-term cognitive outcomes and determine whether the initial symptomatology can predict long-term cognitive problems. Cognitive evaluations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 80 publications
1
8
0
3
Order By: Relevance
“…Our results align with previous studies that have identified a correlation between COVID-19 severity and subsequent declines in physical health (Flegr & Latifi, 2023; Han, Zheng, Daines, & Sheikh, 2022; Iqbal et al, 2021; Mizrahi et al, 2023), mental health challenges (Putri, Arisa, Hananto, Hariyanto, & Kurniawan, 2021; Shanbehzadeh, Tavahomi, Zanjari, Ebrahimi-Takamjani, & Amiri-Arimi, 2021; Zeng et al, 2023), and cognitive deficits (Ariza et al, 2023; Guo et al, 2022; Miskowiak et al, 2021). Collectively, these findings suggest that individuals with a history of more severe COVID-19 symptoms typically face more pronounced post-infection complications.…”
Section: Discussionsupporting
confidence: 92%
“…Our results align with previous studies that have identified a correlation between COVID-19 severity and subsequent declines in physical health (Flegr & Latifi, 2023; Han, Zheng, Daines, & Sheikh, 2022; Iqbal et al, 2021; Mizrahi et al, 2023), mental health challenges (Putri, Arisa, Hananto, Hariyanto, & Kurniawan, 2021; Shanbehzadeh, Tavahomi, Zanjari, Ebrahimi-Takamjani, & Amiri-Arimi, 2021; Zeng et al, 2023), and cognitive deficits (Ariza et al, 2023; Guo et al, 2022; Miskowiak et al, 2021). Collectively, these findings suggest that individuals with a history of more severe COVID-19 symptoms typically face more pronounced post-infection complications.…”
Section: Discussionsupporting
confidence: 92%
“…Our result aligns with prior research which has also identified certain measures of executive function allowing to distinguish nondemented older adults who subsequently experience global cognitive decline from those who maintain cognitive stability (Clark et al, 2012; Junquera et al, 2020). However, a decline in executive function is not specific to AD, as it can also occur in other neurodegenerative conditions such as Parkinson’s disease (Levy et al, 2002), frontotemporal dementia (Hornberger et al, 2008), as well as in nondegenerative conditions such as depression (Nuño et al, 2021), anxiety (Shields et al, 2016), and even COVID-19 (Ariza et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Un metaanálisis realizado por Premraj et al (2022) informó brain fog en 36% de los pacientes pos-covid-19, seguida de problemas de memoria (29%) y de atención (22%). Recientemente, Ariza et al (2023) reportaron compromiso, a largo plazo, de la cognición global, funciones ejecutivas y cognición social.…”
Section: Alteraciones Del Snc Pos-covid-19unclassified